Big Brother’s Little Helpers: The Right to Privacy and the Responsibility of Internet Service Providers - Yael Ronen (Utrecht Journal of International and European Law, 2015)
Following the 2013 revelations on the extent of intelligence gathering through internet service providers, this article concerns the responsibility of internet service providers (ISPs) involved in disclosure of personal data to government authorities under the right to privacy, by reference to the developing, non-binding standards applied to businesses under the Protect, Respect and Remedy Framework. The article examines the manner in which the Framework applies to ISPs and looks at measures that ISPs can take to fulfil their responsibility to respect the right to privacy. It utilizes the challenges to the right to privacy to discuss some aspects of the extension of human rights responsibilities to corporations. These include the respective roles of government and non-state actors, the extent to which corporations may be required to act proactively in order to protect the privacy of clients, and the relevance of transnational activity.